A, FROM Dari Rentan menjadi Tangguh: Eksplorasi Faktor Protektif Kesehatan Mental Penderita TBC Paru-HIV - Ibnu, Indra Fajarwati; Riskiyani, Shanti; Syam, Rizky Chaeraty; Syafar, Muhammad (Fakultas Psikologi Universitas YARSI, 2025)
Tuberculosis (TB) and HIV infections are significant health issues in Makassar City, where their prevalence is increasing and having a substantial impact on individuals' physical and mental health. Poor mental health among TB Paru-HIV patients can exacerbate their physical conditions and hinder the healing process. This study aims to explore the protective factors that contribute to the mental health of patients. The research employs a qualitative approach through in-depth interviews and focus group discussions involving 10 participants. The study was conducted at several hospitals and community health centers in Makassar that provide services for TB Paru-HIV patients, reaching a diverse range of individuals with varying educational and occupational backgrounds. The findings indicate that social support from family and the community serves as an essential emotional safety net, helping patients cope with stigma and anxiety. Access to quality healthcare enhances patients' self-confidence and hope, while involvement in community activities provides a sense of purpose and belonging. Knowledge about the diseases also facilitates understanding and management of their conditions. These findings emphasize the importance of integrating mental health programs into TB Paru-HIV care and the need for community-based interventions to improve patients' psychological well-being. This research provides valuable insights for developing more effective strategies to support the mental health of TB Paru-HIV patients in Makassar.